Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1049/iet-pel.2017.0147
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding instabilities in power electronic systems: toward an on‐chip implementation

Abstract: The available controller chips for power electronic systems are used for specific transient and steady-state performances. In such systems, the parameter ranges for stable operation are delimited by slow-timescale as well as fast-timescale instabilities. The usual practice is to design the control loop based on the state-space averaging technique, which cannot predict the fast-timescale instabilities. In this paper the first attempt has been made to propose a new design of the controller chip that can suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…Past research efforts in [19][20][21][22][23][24][25][26] have analysed and modelled the fast-scale stability status of CMC. Analytical stability boundary for different types of controllers in CMC is computed in [27][28][29][30].…”
Section: Overview Of Interval-1 and Interval-2 Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…Past research efforts in [19][20][21][22][23][24][25][26] have analysed and modelled the fast-scale stability status of CMC. Analytical stability boundary for different types of controllers in CMC is computed in [27][28][29][30].…”
Section: Overview Of Interval-1 and Interval-2 Samplingmentioning
confidence: 99%
“…3.1.1 Interval-2 sampling: Using 12, (14), and (22) with m c = 0 and t 1 = 0, the current-loop model can be derived, and the perturbed discrete-time current-loop model becomes…”
Section: Stability Analysis Using Different Sampling Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In Ref. 23, a controller is proposed that forces the system to have more than two switchings during a period in an attempt to avoid subharmonic behaviors in complex converters; however, as the switching time increases, faster devices are needed and the durability of the elements decreases. Other studies that include both fast scale and slow scale instabilities are reported in Refs.…”
Section: Introductionmentioning
confidence: 99%